2022
DOI: 10.1111/jocs.16563
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for respiratory failure in phases of COVID‐19 variants

Abstract: Background Adaptive mutations of the severe acute respiratory syndrome‐related coronavirus (SARS‐CoV‐2) virus have emerged throughout the coronavirus disease 2019 (COVID‐19) pandemic. The characterization of outcomes in patients requiring extracorporeal membrane oxygenation (ECMO) for severe respiratory distress from COVID‐19 during the peak prevalence of different variants is not well known. Methods There were 131 patients with laboratory‐confirmed SARS‐CoV‐2 infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Although there was wide variability in the patient age groups across studies, many studies reported the average age of the patient to be in the fourth decade of life like those in our study. [6][7][8] However, few studies observed that the patients were nearly a decade older than those in our study. [9][10][11] The literature on the effect of a higher age on mortality is inconclusive.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although there was wide variability in the patient age groups across studies, many studies reported the average age of the patient to be in the fourth decade of life like those in our study. [6][7][8] However, few studies observed that the patients were nearly a decade older than those in our study. [9][10][11] The literature on the effect of a higher age on mortality is inconclusive.…”
Section: Discussioncontrasting
confidence: 56%
“…Many of the authors reported a high BMI (>30) in their study group. 8,9,11,13 All these studies came from the Western world which is nutritionally better than Indian subcontinent. This explains why BMI was higher in the cited studies as compared to our study population.…”
Section: Discussionmentioning
confidence: 99%
“…While nine-month mortality of patients requiring tracheostomy during hospitalization for COVID-19 has been reported to be up to 70%, recent data suggest that those undergoing tracheostomy after intubation for COVID-related ARDS have decreased mortality compared to intubated patients who did not receive a tracheostomy [ 18 , 19 ]. Furthermore, much of the published literature suggests better outcomes associated with early tracheostomy, defined as tracheostomy performed within 7-14 days of endotracheal intubation [ 2 , 3 , 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to the timing of tracheostomy for patients on ECMO, there are conflicting reports surrounding the benefit of early tracheostomy, in part due to an overall poor prognosis. One study of 131 patients who were cannulated for VV-ECMO demonstrated better outcomes for earlier ECMO cannulation and earlier tracheostomy placement [ 16 ]. However, another series showed that patients who were on ECMO suffered higher rates of hemorrhagic complications after undergoing early tracheostomy and did not achieve better outcomes [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…ECMO has been successfully used to manage pregnant patients in critical condition [ 5 , 7 , 8 ]. Potential indications for ECMO in pregnant women are pulmonary embolism, amniotic fluid embolism, cardiomyopathy, and primary pulmonary hypertension with right heart failure [ 9 ].…”
Section: Discussionmentioning
confidence: 99%